Use of ultimate strength techniques for fire resistant design of offshore structures (Steel Construction Institute, 1995)
'This Technical Note has been prepared to focus on the subject of progressive collapse. In order to provide guidance for selection and use of a suitable progressive collapse analysis system and progressive collapse modeling, this document introduces the basic theory behind progressive collapse and presents various methods for performing a progressive collapse analysis. It also gives practical examples of application of progressive collapse techniques. The document is set out in a logical manner and considers in turn the setting of performance standards to meet the present goal setting approach to safety on offshore installations, the thermal response of structures and components, the strength response of structures and components, combined effects and finally examples describing various approaches."--Knovel.
At head of title: Technical note and worked examples to supplement the Interim guidance notes for the design and protection of topside structures against explosion and fire.
'This document is a deliverable of the Fire And Blast Information Group (FABIG)--for the year April 1994 - March 1995."
Keywords: Structural failures -- Prevention.; Structural failures -- Risk assessment.; Offshore structures -- Design and construction.; Offshore structures -- Fires and fire prevention.; Drilling platforms -- Design and construction.; Drilling platforms -- Fires and fire prevention.; elektronické knihy; electronic books